Mesoporous concentric magnetic FePt core-shells nanoparticle with functionalized surfaces for capturing metal ions and DNA molecules. - Tang, H; Qian, Y; Ren, Y; Chen, H; Jones, I; Yue, B; Hel, H; Tsang, S (2009)
It is demonstrated that monodisperse magnetic FePt nanoparticle can be engineered into a protective dense silica layer, followed by concentric outer mesoporous silica layers with tailored -SH, -SO3H and -NH2 surface groups, these new materials can be used to capture heavy metal ions and DNA molecules from solution specifically by their internal or/and external functionalised surfaces by magnetic means.